Pembangunan Aplikasi Monitoring dan Seleksi Atlet (Studi Kasus: Cabang Olahraga Basket, Sepak Bola, dan Bola Voli) - Helfi Pangestu; Bayu Priyambadha; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sport is an activity which can improve someone's health. Indonesia government creates an organization that aims to accommodate people based on their hobbies especially in sport. Organization scale is not only national but also available in campus. Beside of accommodating people, the organization aims gathering people who has good potential. To select and monitor prospective athlete, organization management do internal sparing. But it is not objective because someone's condition can not only monitor by once or twice workout. In case continually monitoring, coach has faced trouble in performance documentation section. It is caused by limited resource. That's why, researcher proposes a system which able to monitor and keep the result using waterfall development method.Result of implementation is; monitoring system and selective athlete has many feature about team management, keeping athlete's achievement, injury history and athlete recommendation. It has built using Model-View-Controller (MVC) structure laravel framework. White-box testing result system and black-box testing result in the amount of validity is 100%.